2020
DOI: 10.1088/2053-1591/ab7e4c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mono-dopants (Mg2+) and co-dopants (Mg2+, Zr4+) on the dielectric, ferroelectric and optical properties of BaTiO3 ceramics

Abstract: In this work, BaTiO3, Ba(Mg0.01Ti0.99)O3, Ba(Mg0.015Ti0.985)O3, Ba(Mg0.02Ti0.98)O3 and Ba(Mg0.01Zr0.15Ti0.84)O3 ceramics have been prepared through conventional solid-state route to investigate the effects of Mg2+ and Zr4+ dopants as mono-substitution (only Mg2+) and co-substitution (Mg2+ and Zr4+) of B-site on the structural, electrical and optical properties of BaTiO3 ceramics. Exhibiting perovskite structure, Ba(Mg x Ti1−x)O3 ceramics revealed a decrement pattern of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Figure 5 shows the optical band gap energies of BTNNO ceramics. The optical band gap (E g ) is deduced via allowed direct inter-band transition between conduction and valence bands by Tauc's relation [28]:…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 shows the optical band gap energies of BTNNO ceramics. The optical band gap (E g ) is deduced via allowed direct inter-band transition between conduction and valence bands by Tauc's relation [28]:…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the dielectric constant of the fabricated Ba 1−2x Ho 2x Ti 1−x Mn x O 3 (x = 0, 0.02, 0.04, and 0.06) piezoceramics has declined by increasing the frequency. Indeed, the dielectric constant of Ba 1−2x Ho 2x Ti 1−x Mn x O 3 (x = 0, 0.02, 0.04, and 0.06) piezoceramics is diminished as the frequency rose owing to the domain wall motion phenomena [53][54][55]. In the entire samples at low frequencies the domain walls in the fabricated Ba 1−2x Ho 2x Ti 1−x Mn x O 3 were moved effortlessly, aligning with the applied electric field, thus elevating the dielectric constant.…”
Section: Dielectric and Piezoelectric Propertiesmentioning
confidence: 99%
“…Conversely, at higher frequencies the electric field oscillated rapidly for the domain walls to keep pace. This impedes their motion and results in a lower dielectric constant [55,56].…”
Section: Dielectric and Piezoelectric Propertiesmentioning
confidence: 99%
“…15 Moreover, Mostari et al demonstrated that Mg 2+ doping in the Ti 4+ site could pin the oxygen vacancy (V O ) by forming the defect complex of Mg 00 Ti À V O and hence improved the reliability of dielectrics. 16 This effect was further enhanced by co-doping with other elements. [17][18][19] Yang et al and Gu et al reported 95BaTiO 3 -2MgO-2CaCO 3 -1Dy 2 O 3 ceramics with their improved breakdown strength, flattened e 0 -T characteristics, and excellent reliability.…”
Section: Introductionmentioning
confidence: 99%